Performance of Mutual Funds in India 2003-2008 - Raizada, Shantanu (2008)
Many studies have been conducted in the past on the performance of Mutual Funds in comparison to the market index. These studies may differ in their time period, but most of them concluded that on an average the Mutual Funds failed to outperform the market thus the Efficient Market Hypothesis holds good. This research was based on the performance of 20 open ended equity diversified growth Mutual Funds for a period of 5 years from April 2003 to March 2008 and was compared to the BSE 500. Funds were evaluated using Sharpe Ratio, Treynor Ratio, Jensen's alpha etc. The results were quite significant and different from the past studies. It was concluded that more than 75% of the funds outperformed the market and delivered positive returns.